2011
DOI: 10.1002/ccd.23002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myocardial ischemic burden following percutaneous coronary intervention of chronic total occlusions

Abstract: Ischemic burden is reduced following CTO PCI, and the decrease is greater at high ischemic burden. A threshold of 12.5% ischemic burden is suggested as a criterion for performing PCI in the setting of CTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 20 publications
1
54
0
3
Order By: Relevance
“…11 In patients without symptoms, the threshold for performing coronary revascularization including CTO-PCI should be considerably higher, yet patients with large areas of ischemia (eg, ischemic burden .12.5%) could also derive benefit from CTO revascularization. 12 Some patients may also be ''asymptomatic'' because they gradually limit their activities to prevent symptoms from appearing.…”
Section: N Benefits Of Cto-pcimentioning
confidence: 99%
“…11 In patients without symptoms, the threshold for performing coronary revascularization including CTO-PCI should be considerably higher, yet patients with large areas of ischemia (eg, ischemic burden .12.5%) could also derive benefit from CTO revascularization. 12 Some patients may also be ''asymptomatic'' because they gradually limit their activities to prevent symptoms from appearing.…”
Section: N Benefits Of Cto-pcimentioning
confidence: 99%
“…Safley et al [38] identified 301 patients who underwent PCI for chronic total occlusion and in whom MPI was performed within 12 ± 3 mo before PCI and a followup study within 12 ± 3 mo after PCI. The change in % ischemia was +5.39% (P = 0.006), -1.70% (P = 0.008), -6.32% (P < 0.001), and -16.26% (P < 0.001) in patients with no/minimal (< 5% ischemic myocardium), mild (5%-9.9%), moderate (10%-16%), and severe (> 16%) ischemia, respectively.…”
Section: Mortality?mentioning
confidence: 99%
“…In a study of 301 patients who underwent myocardial perfusion imaging before and after CTO PCI, a baseline ischaemic burden of >12.5 % was optimal in identifying patients most likely to have a significant decrease in ischaemic burden post-CTO PCI, suggesting that the highest benefit of CTO PCI is more likely to be achieved in patients with significant baseline myocardial ischaemia. 69 …”
Section: Completeness Of Coronary Revascularisation and Outcomesmentioning
confidence: 99%